2023
DOI: 10.1007/s40820-023-01254-8
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Patterning Strategies for Full-Color Perovskite Light-Emitting Diodes

Gwang Heon Lee,
Kiwook Kim,
Yunho Kim
et al.

Abstract: Metal halide perovskites have emerged as promising light-emitting materials for next-generation displays owing to their remarkable material characteristics including broad color tunability, pure color emission with remarkably narrow bandwidths, high quantum yield, and solution processability. Despite recent advances have pushed the luminance efficiency of monochromic perovskite light-emitting diodes (PeLEDs) to their theoretical limits, their current fabrication using the spin-coating process poses limitations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(3 citation statements)
references
References 269 publications
0
3
0
Order By: Relevance
“…48 The C−N heads of organic cations are embedded into the open cavities in the inorganic skeleton through hydrogen bonding interaction (Figure S3). The bond lengths between Pb and Cl atoms are varied from 2.845 (4) to 2.910 (4) Å, and the range of bond angles is from 85.37 (11) to 176.48 (13)°. Organic cations as "spacers" are neatly arranged between two adjacent infinite 2D inorganic frameworks composed of corner-shared distorted [PbCl 6 ] octahedral units.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…48 The C−N heads of organic cations are embedded into the open cavities in the inorganic skeleton through hydrogen bonding interaction (Figure S3). The bond lengths between Pb and Cl atoms are varied from 2.845 (4) to 2.910 (4) Å, and the range of bond angles is from 85.37 (11) to 176.48 (13)°. Organic cations as "spacers" are neatly arranged between two adjacent infinite 2D inorganic frameworks composed of corner-shared distorted [PbCl 6 ] octahedral units.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Multiferroic was initially coined by Aizu in 1968 with the theoretical identification of 42 species of simultaneously ferroelectric and ferroelastic phase transition . The famous inorganic Gd 2 (MoO 4 ) 3 with the fully ferroelectric–fully ferroelastic effect was predicted and successfully validated in 1968, serving as a typical model for fully multiferroic over subsequent decades. , The characteristic of a type of ferroelectric–ferroelastic crystal is that the concurrent alteration of the polarization vector alongside changes in the strain tensor, and vice versa, is fully ferroelectric and fully ferroelastic. Capitalizing on these dual ferroic effects, the development of high-precision electronic micropositioners, tunable radio frequency filters, compatible grating devices, and adaptive devices has become feasible. Furthermore, the synergy between ferroelectricity and ferroelasticity can markedly enhance material physical properties. , For example, You et al reported a hybrid perovskite multiferroic [Me 3 NCH 2 Cl]­CdCl 3 , whose illustrious electromechanical conversion performance has been proven to be closely related to the partial coupling of ferroelectricity and ferroelasticity. , Benefiting from the numerous advantages of intimate interplay between full ferroelectricity and full ferroelasticity, recently, a large amount of studies have focused on exploring multiferroic materials with ferroelectricity and ferroelasticity. However, constructing ferroelectric that is compatible with ferroelasticity has been a great challenge due to the strict requirements of crystallographic symmetry, reasonable symmetry breaking, and ingenious evolution of lattice parameters. …”
Section: Introductionmentioning
confidence: 99%
“…Metal halide perovskites (MHPs) have been the subject of considerable academic interest over the past decade, due to their exceptional photoelectric properties, including the high light-absorption coefficient, long diffusion length of charge carriers, and tunable optical bandgap, which make them promising as the active media for a range of high-efficiency photoelectric devices, such as solar cells, light-emitting diodes, and photodetectors. MHP is typically formulated as ABX 3 , where A, B, and X represent monovalent cation, bivalent metal cation, and halide anion, respectively . Given the intrinsically low formation energy of structural distortion, MHPs generally suffer from soft lattice and deformable structures .…”
mentioning
confidence: 99%